Forest Conservation by Conserving Socio-cultural Aspects: A Lesson from the Sougb Tribe in Teluk Bintuni, West Papua Province - Rumayomi, Nimrod Agustinus Andyratnah; Murdjoko, Agustinus; Ungirwalu, Antoni; Mulyadi; Benu, Nithanel Mikael Hendrik; Djitmau, Dony Aristone (Jurnal Manajemen Hutan Tropika, 2025)
Forest has been part of local people such as Sougb Tribe for generations where at the same time they have applied the traditional knowledge. However, the local government has been conducting development for decades with less involvement of the local knowledge. Hence, this research aimed to figure out the traditional knowledge during the forest utilization by Sougb Tribe in Teluk Bintuni, West Papua Province. The data were collected using interviews with the snowball method in subdistricts of Bintuni, Bintuni Timur, Manimeri, Tuhiba, and Tembun. Then, the study revealed that the Sougb Tribe, originally part of the Arfak Tribe, has inhabited the Teluk Bintuni area for generations, migrating from the highlands to the lowlands due to various factors like marriage and conflict. They still maintain customary rights while managing the land through traditional organizations. This tribe relies profoundly on forest resources for sustenance, practicing sustainable agriculture and traditional hunting. Despite facing challenges in forest utilization, they emphasize the importance of biodiversity and traditional knowledge in local conservation. Thus, it is vital to integrate this local wisdom into regional development that can enhance sustainability and cultural preservation, fostering community engagement and ecological balance.